Using the Community of Inquiry Framework to Scaffold Online Tutoring - Feng, Xiaoying; Xie, Jingjing; Liu, Yue (International Review of Research in Open and Distributed Learning, 2017)
Tutoring involves providing learners with a suitable level of structure and guidance to support their learning. This study reports on an exploration of how to design such structure and guidance (i.e., learning scaffolds) in the Chinese online educational context, and in so doing, answer the following two questions: (a) What scaffolding strategies are needed to design online tutoring, and (b) How should different levels of scaffolding intensity be emphasized in different stages of online tutoring in such educational contexts? A model for online tutoring using the Community of Inquiry framework was developed and implemented in this study. It focused attention on both the critical role of the tutor in online learning and the importance of scaffolding in online tutoring. Both qualitative and quantitative methods were used to collect data, including questionnaires, interviews, and content analysis. In considering the variation of scaffolding throughout the online course, results showed that: (a) As long as a high degree of social presence is established in the initial phase, scaffolds for social presence can be withdrawn gradually throughout the course; (b) High-intensity teaching presence is much more important in the mid-phase of the course than in other phases; (c) “Discourse facilitation” should be emphasized for teaching presence in the mid-phase, while “direct instruction” scaffolding is needed in the last phase; and (d) The greatest need for scaffolding of cognitive presence occurs in the final phase of the course.